(untitled) (Journal of Ideas in Health, 2022)
Background: The short- and long-term outcomes of thrombolysis has been predicted by various scores and models based on the electrocardiogram. This study aimed to compare various mortality predictors in ST-elevation myocardial infarction (STEMI) patients undergoing thrombolysis. Methods: A prospective, case-control, single-center study was performed at MGM Hospital, Warangal, India, between November 2019 and November 2021. A total of 100 STEMI patients were enrolled, out of which 50 were controls (patients who survived after seven days of thrombolysis) and 50 were cases (patients who died after seven days of thrombolysis). Aldrich score, TIMI risk index (TRI), Sclarovsky-Birnbaum Ischemia Grading (SB-IG) algorithm, presence of Q waves, total ST-segment deviation, and the number of leads with ST-segment elevation (STE) in anterior wall MI (AWMI) were calculated. Results: The mean age of the case group was 55.3 ± 11.6 years, and that of the control group was 55.5 ± 10.1 years. Males comprised 46.0% and 66.0% of the case and control groups. The c-statistic of TRI was found to be the highest (c = 0.68; P = 0.001), followed by the SB-IG algorithm (c = 0.58; P = 0.021), the sum of R waves in AWMI (c = 0.5; P = 0.019), the number of leads with STE in AWMI (c = 0.47; P = 0.778), total ST-segment deviation (c = 0.47; P = 0.552), Aldrich score for AWMI (c = 0.43; P = 0.590), presence of Q waves (c = 0.40; P = 0.676), and Aldrich score for inferior wall MI (c = 0.32; P = 0.071). Conclusion: TRI and SB-IG algorithms had moderate accuracy in predicting seven-day mortality in STEMI patients undergoing thrombolysis. Other scores and parameters viz. Aldrich score, presence of Q waves, total ST-segment deviation, and the number of leads with STE in AWMI had very poor accuracy in predicting in-hospital outcomes. More extensive studies with longer durations are required to validate our findings.